1988
DOI: 10.1016/0165-1781(88)90072-8
|View full text |Cite
|
Sign up to set email alerts
|

EEG sleep and the cholinergic REM induction test in anorexic and bulimic patients

Abstract: Abstract. The electroencephalographic (EEG) sleep of 20 anorexic patients, 10 bulimic patients, and 10 age-matched healthy controls was studied. In addition, six anorexic patients and six bulimic patients had a cholinergic rapid eye movement (REM) sleep induction test (RIT) performed with the cholinergic agent RS 86. The three samples showed no major differences in sleep patterns. The same held true when attention was focused on patients who additionally met D&U-Illcriteria for major depression. The RIT result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1
2

Year Published

1989
1989
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 31 publications
1
25
1
2
Order By: Relevance
“…In healthy volunteers, the REM sleep inducing properties of RS 86 were proved by Spiegel (1984) and Riemann et al (1988). Berger et al (1985Berger et al ( , 1989 demonstrated that the effect of RS 86 on REM sleep regulation was significantly more pronounced in patients with major depression than in patients with other psychiatric disorders and healthy volunteers, supporting the hypothesis of a functional hypersensitivity of the cholinergic system during depression.…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…In healthy volunteers, the REM sleep inducing properties of RS 86 were proved by Spiegel (1984) and Riemann et al (1988). Berger et al (1985Berger et al ( , 1989 demonstrated that the effect of RS 86 on REM sleep regulation was significantly more pronounced in patients with major depression than in patients with other psychiatric disorders and healthy volunteers, supporting the hypothesis of a functional hypersensitivity of the cholinergic system during depression.…”
Section: Introductionmentioning
confidence: 91%
“…In the latter two studies, all patients exhibiting a shortened REM latency suffered from a significant depressive mood disturbance. On the other hand, Levy et al (1987Levy et al ( , 1988, Hudson et al (1987) and Lauer et al (1988) found no altered REM sleep patterns in anorexic and bulimic patients, regardless of the coexistence of a minor or major depression. However, the majority of these investigations had the disadvantage of not including a comparison group of patients with major depression.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations